2010
DOI: 10.2223/jped.1976
|View full text |Cite
|
Sign up to set email alerts
|

Maternal consumption of flaxseed during lactation affects weight and hemoglobin level of offspring in rats

Abstract: Objective: To investigate the effects of maternal flaxseed consumption during lactation on the body weight, hematological indicators and visceral fat mass of male offspring in adulthood. Methods:Sixteen female Wistar rats were divided into two groups after giving birth. During lactation the control group (CG) was fed a casein-based diet and the flaxseed group (FG) was fed a casein-based diet containing 25% flaxseed. After weaning, male offspring were fed on commercial chow until adulthood and euthanized at 170… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
2
4
0
1
Order By: Relevance
“…However, they showed higher body fat mass than the control group (þ28 per cent, p < 0.0001). Same result was found by Cardozo et al (2010) at 170 days of life in relation to body mass; however, no differences were found in the visceral fat mass between groups. However, Brant et al (2012) observed that the offspring that consumed diet with 25 per cent of flaxseed after weaning and whose mothers consumed flaxseed diet during lactation showed lower body mass at 200 days of life as compared to control group (p = 0.001), corroborating with Cardozo et al (2011), which found a significant reduction in body mass as compared to the animals of the control group at 250 days of life.…”
Section: Effects On Body Masssupporting
confidence: 75%
See 1 more Smart Citation
“…However, they showed higher body fat mass than the control group (þ28 per cent, p < 0.0001). Same result was found by Cardozo et al (2010) at 170 days of life in relation to body mass; however, no differences were found in the visceral fat mass between groups. However, Brant et al (2012) observed that the offspring that consumed diet with 25 per cent of flaxseed after weaning and whose mothers consumed flaxseed diet during lactation showed lower body mass at 200 days of life as compared to control group (p = 0.001), corroborating with Cardozo et al (2011), which found a significant reduction in body mass as compared to the animals of the control group at 250 days of life.…”
Section: Effects On Body Masssupporting
confidence: 75%
“…Soares et al (2010), Leite et al (2012), Brant et al (2012) and da Costa et al (2016a offered during lactation, diet with 25 per cent of flaxseed and observed that both female and male offspring of these dams at weaning showed the same body mass when compared to the offspring of control dams. However, Cardozo et al (2010), Troina et al (2010) and Fernandes et al (2011), when analysing male offspring at weaning, observed a body mass reduction (p = 0.04, p < 0.05 and p < 0.05, respectively) when compared to offspring of dams who consumed control diet, and this finding agreed with Collins et al (2003), which showed that after providing diet with different defatted flaxseed concentrations, verified lower body mass in this offspring when compared to control group. Only one study observed higher body mass at 21 days of life in the male offspring of dams who consumed 25 per cent flaxseed diet when compared to control group (da Costa et al, 2016a(da Costa et al, , 2016b.…”
Section: Effects On Body Masssupporting
confidence: 69%
“…[21][22][23][24] In our study, although no statistically difference was found, a trend to lower body mass in animals of rat dams that consumed flaxseed diet during lactation was found. Other studies [25][26][27] reported lighter body mass of male offspring of rat dams who consumed flaxseed diet when compared to offspring of rat dams who consumed a control diet. The lower fat mass of these animals is probably the responsible component for the lower body mass at weaning, since animals did not show changes in other compartments of the body.…”
Section: Discussionmentioning
confidence: 92%
“…The artery was dissected from the aortic arch, and the aorta was sectioned transversely with transverse cuts in the distal end of the sections. Later, the pieces of aorta were fixed in buffered formalin at 10% (Millonnig formalin) for 24 hours, and processed with a standard technique of paraffin inclusion, as described by Pereira et al 25 Subsequently, the paraffin blocks containing the pieces of aorta were cut using a CUT 4050 microtome (Microtec®), in sections of 5µm, stained with hematoxylin and eosin, and Weigert's Resorcin-Fuchsin for later evaluation.…”
Section: Histomorphometric Analysis Of the Aortamentioning
confidence: 99%
“…No estudo realizado com filhotes, aos 21 dias de vida, da mesma raça, porém da linhagem Wistar, foi observado que os animais oriundos de mães que também receberam ração acrescida de 25% da semente de linhaça tiveram peso corporal menor do que o GC (GC = 47,31±4,72 g; GL = 42,69±3,06 g), assim como menor evolução ponderal (GC = 41,45±4,81; GL = 36,55±3,82) 23 . Tais resultados são contraditórios ao dado experimento, tanto no peso corporal (GC = 32,6±7,5 g; GL = 37±6,96 g) quanto na evolução ponderal (GC = 27,7±7,5; GL = 31,8±7,0).…”
Section: Tabela 2 -Consumo De Ração Das Ratas Número De Crias E Cremunclassified